Alpha-Lipoic Acid Protects Co-Exposure to Lead and Zinc Oxide Nanoparticles Induced Neuro, Immuno and Male Reproductive Toxicity in Rats - Deore, Monika S.; S, Keerthana; Naqvi, Saba; Kumar, Anoop; Flora, S. J. S. (Frontiers in Pharmacology, 2021)
We evaluated neuro, immuno and male reproductive toxicity of zinc oxide nanoparticles (ZnO NPs) alone, and in combination with lead acetate and also studied the therapeutic role of α-lipoic acid. Lead (10 mg/kg body weight), ZnO NPs (100mg/kg bwt) alone and their combination were administered orally in Wistar rats for 28 days followed by 15 days treatment of α-lipoic acid (15mg/kgbwt). Our results demonstrated protective effect of lipoic acid on lead and ZnO NPs induced neurological, immunological and male reproductive alterations in rats. The altered level of blood δ-aminolevulinic acid dehydratase (ALAD), immunoglobulins (IgA, IgG, IgM, IgE), interleukins (IL-1β, IL-4, IL-6), caspase-3, and tumor necrosis factor (TNF-α) were attenuated by lipoic acid treatment. The lead and ZnO NPs induced oxidative stress was decreased by lipoic acid treatment. Alteration in normal histological architecture of brain section (cortex and hippocampus), and testes further confirmed neuro and male reproductive toxicity of lead and ZnO NPs, while lipoic acid treated group restored normal architecture. We observed a decrease in blood metal content in lipoic acid treatment group as compared to lead administered group which indicate moderate chelating property of lipoic acid. Our study suggests that lipoic acid could be a promising agent against lead and ZnO NPs altered neurological, immunological and reproductive parameters.